1992
DOI: 10.2307/3869543
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and Meiotic Chromosomal Recombination between Inverted Duplications in Transgenic Tobacco Plants

Abstract: Homologous recombination has been extensively studied in bacteria, yeast, and more recently in animal cells, but little is known about this process in plants. We present here an analysis of meiotic and somatic chromosomal recombination between closely linked inverted duplications located on a single chromosomal region in tobacco. Transgenic tobacco lines were constructed by Agrobacterium transformation with plasmid vectors containing a functional hygromycin phosphotransferase (hyg) selectable marker flanked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
3
30
0
Order By: Relevance
“…It has been shown that in plants homologous recombination can be stimulated by genomic stress caused by x-rays, mitomycin C, and MMS treatments (9)(10)(11). This indicates that homologous recombination is involved, at least in part, in the repair of the DNA damage caused by these agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that in plants homologous recombination can be stimulated by genomic stress caused by x-rays, mitomycin C, and MMS treatments (9)(10)(11). This indicates that homologous recombination is involved, at least in part, in the repair of the DNA damage caused by these agents.…”
Section: Discussionmentioning
confidence: 99%
“…As in other organisms (5), the frequency of meiotic recombination in plants is influenced by environmental factors (6), sequence diversity in interspecific crosses (7), and the direction of crossing (8). In somatic cells, rates of homologous recombination can be stimulated by DNA-damaging treatments (9)(10)(11). This also has been observed in bacteria, yeast, and mammalian cells (12).…”
mentioning
confidence: 88%
“…Unfortunately, the number of events was so small that it is not possible to obtain good GT frequency estimates. Low frequencies of HR also have been reported when quantification was done for intrachromosomal recombination (ICR) in tobacco and Arabidopsis (14)(15)(16). Similarly, the rate of somatic crossover between homologous chromosomes was shown to be very low (17,18).…”
Section: ϫ5mentioning
confidence: 93%
“…In Table 1, only those kanamycin-resistant calli that proved to be the result of homologous recombination events are listed (see below). However, we also obtained calli (one for lines 1-7 and 1-12 each and nine for line [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] in which the kanamycin resistance was either due to illegitimate recombination events (molecular data not shown) or "escapes." Illegitimate recombination leading to kanamycin resistance may be explained by unexpected splicing of the intron sequence, whereas escapes may have arisen due to the relatively weak kanamycin selection, which had to be applied due to the relatively low level of resistance expressed by the artificial kanamycin construct (23).…”
Section: Methodsmentioning
confidence: 99%
“…However, several lines of indirect evidence indicate that transient DSBs enhance homologous recombination. Factors that introduce unspecific DSBs in DNA, such as x-rays (15,16) or methyl methanesulfonate (17), were shown to enhance intrachromosomal homologous recombination in plants. Excision of transposable elements was correlated with increased frequencies of recombination at the donor site between repeats flanking the element (18,19) or between repeats at ectopic sites (A.…”
mentioning
confidence: 99%